Results difference in elite short track speed skating on European and World championships in women`s and men`s 500m - Kolenc, M.; Milanovic, D.; Nikolic, B. (World Congress of Performance Analysis of Sport XII, 2018)
European and World championships, like In any other sport, are right behind Olympic games by competitiveness In short track speed skating. Considering that different athletes compete on these two Championships, mental requirement and motivation Is different, one could assume that there must be a statistlcaly significant difference between results. We made a hypothesis that there are statistlcaly significant differences between results In 500m on European and World championship, for women and men separately. Statistical analysis was done on gathered data (Kolmogorov-Smlrnovljev, Shaplro-Wllkov and T-test), which showed that there are no statlslcaly significant difference between European and World championship results In men`s and women`s 500m. There are number of reasons for that phenomenon, which are described In the paper.